Accident Analysis Modeling and Case Study of Hydrogen Refueling Station Using Root Cause Analysis (RCA) - Il Jae Lee; A Ran Lee; Kyung-Sun Lee (Safety, 2025)
As the global transition to carbon neutrality accelerates, hydrogen energy has emerged as a key alternative to fossil fuels due to its potential to reduce carbon emissions. Many countries, including Korea, are constructing hydrogen refueling stations; however, safety concerns persist due to accidents caused by equipment failures and human errors. While various accident analysis models exist, the application of the root cause analysis (RCA) technique to hydrogen refueling station accidents remains largely unexplored. This study develops an RCA modeling map specifically for hydrogen refueling stations to identify not only direct and indirect causes of accidents, but also root causes, and applies it to actual accident cases to provide basic data for identifying the root causes of future hydrogen refueling station accidents. The RCA modeling map developed in this study uses accident cause investigation data from accident investigation reports over the past five years, which include information on the organizational structure and operational status of hydrogen refueling stations, as well as the RCA handbook. The primary defect sources identified were equipment defect, personal defect, and other defects. The problem categories, which were the substructures of the primary defect source “equipment defect,” consisted of four categories: the equipment design problem, the equipment installation/fabrication problem, the equipment reliability program problem, and the equipment misuse problem. Additionally, the problem categories, which were the substructures of the primary defect source “personal defect,” consisted of two categories: the company employee problem and the contract employee problem. The problem categories, which were the substructures of the primary defect source “other defects,” consisted of three categories: sabotage/horseplay, natural phenomena, and other. Compared to existing accident investigation reports, which identified only three primary causes, the RCA modeling map revealed nine distinct causes, demonstrating its superior analytical capability. In conclusion, the proposed RCA modeling map provides a more systematic and comprehensive approach for investigating accident causes at hydrogen refueling stations, which could significantly improve safety practices and assist in quickly identifying root causes more efficiently in future incidents.